2021
DOI: 10.19044/esj.2021.v17n23p296
|View full text |Cite
|
Sign up to set email alerts
|

Cost Leadership Strategy: A New Game Strategy for Competitive Advantage in Milk Processing Firms in Kenya

Abstract: Competitive advantage refers to the benefits that firms accrue from unique combination of possessions to outperform competitors. To build competitive advantage as a gateway to superior performance, firms pursue various beneficial strategic orientations. This study sought to establish whether cost leadership strategy gave rise to competitive advantage in milk processing firms in Kenya. The authors utilized the indicators of economies of scale, economies of scope and operational efficiency to operationalize cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…So, the competitive strategy is limited to cost leadership strategy and differentiation strategy in this study. The empirical research of many scholars show that it can improve firm performance if firms make clear competitive strategies [6], but some results have showed that the competitive strategy is irrelevant or weakly relevant to firm performance. Some researchers find that competitive strategy does not directly affect the performance of a firm by examining the performance of Ghana's manufacturing companies, but it indirectly affects the performance of the business through a positive correlation of the manufacturing strategy.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…So, the competitive strategy is limited to cost leadership strategy and differentiation strategy in this study. The empirical research of many scholars show that it can improve firm performance if firms make clear competitive strategies [6], but some results have showed that the competitive strategy is irrelevant or weakly relevant to firm performance. Some researchers find that competitive strategy does not directly affect the performance of a firm by examining the performance of Ghana's manufacturing companies, but it indirectly affects the performance of the business through a positive correlation of the manufacturing strategy.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Selain itu, strategi kepemimpinan biaya telah diidentifikasi sebagai elemen kunci keunggulan kompetitif (Kimiti, A. Muathe, and Murigi 2021). Dengan menerapkan teknologi hemat biaya dan mengoptimalkan proses operasional, operator dapat memposisikan organisasi mereka sebagai pemimpin industri dalam hal profitabilitas.…”
Section: Strategi Kepemimpinan Dalam Mengintegrasikan Teknologi Dan S...unclassified
“…Ngah & Wong (2020) analyzed the effect of knowledge management in formulating competitive strategies for knowledge-based small-and medium-sized enterprises (SMEs) in Malaysia using a quantitative approach of a survey conducted on 135 owners and managers of knowledge-based SMEs in Malaysia. Kimiti et al (2021) analyzed the cost leadership strategy that can contribute to competitive advantage. Various competitive strategies have been examined, revealing that firms can achieve a competitive advantage by responding to external factors such as competitors and customers (Dedan et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%